Biodegradable aniline-derived electroconductive film for the regulation of neural stem cell fate. Issue 5 (14th January 2021) - Chao, Keui-Yu; Huang, Wei-Yuan; Ho, Chia-Yu; Wan, Dehui; Wang, Huan-Chih; Yang, Chun-Yi; Wang, Tzu-Wei
Abstract : Schematic of biodegradable aniline-derived electroconductive film (4a-PLAAP) for the modulation of neural stem cells (NSCs) behavior. Abstract : Neural stem cells (NSCs) represent significant potential and promise in the treatment of neurodegenerative diseases and nerve injuries. An efficient methodology or platform that can help in specifically directing the stem cell fate is important and highly desirable for future clinical therapy. In this study, a biodegradable electrical conductive film composed of an oxidative polymerized carboxyl-capped aniline pentamer (CCAP) and ring-opening polymerized tetra poly(d, l -lactide) (4a-PLA) was designed with the addition of the dopant, namely chondroitin sulfate. This conductive film acts as a biological substrate for the exogenous/endogenous electric field transmission in tissue, resulting in the control of NSC fate, as well as improvement in neural tissue regeneration. The results show that CCAP is successfully synthesized and then conjugated onto 4a-PLA to form a network structure with electrical conductivity, cell adhesion capacity, and biodegradability. The neuronal differentiation of NSCs can be induced on 4a-PLAAP, and the neuronal maturation process can be facilitated by the manipulation of the electrical field. This biocompatible and electroactive material can serve as a platform to determine the cell fate of NSCs and be employed in neural regeneration. For future perspectives, its promising performance shows potential in applications, such as electrode-tissue integration interfaces, coatings on neuroprosthetics devices and neural probes, and smart drug delivery system in neurological systems.